2017
DOI: 10.1101/gr.218669.116
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration stress extends mRNA 3′ untranslated regions with noncoding RNA functions in Arabidopsis

Abstract: The 3 ′ untranslated regions (3 ′ UTRs) of mRNAs play important roles in the regulation of mRNA localization, translation, and stability. Alternative cleavage and polyadenylation (APA) generates mRNAs with different 3 ′ UTRs, but the involvement of this process in stress response has not yet been clarified. Here, we report that a subset of stress-related genes exhibits 3 ′ UTR extensions of their mRNAs during dehydration stress. These extended 3 ′ UTRs have characteristics of long noncoding RNAs and likely do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…Recently, it has been reported that dehydration stress promotes the extension of 3′‐UTR of mRNAs. Although they have characteristics of long non‐coding RNAs, they instead act as antisense RNA to regulate gene transcription (Sun et al ., ). It could be possible that non‐canonical mRNA isoforms might, in some cases, act as miRNA repressors or other sorts of RNA regulators.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been reported that dehydration stress promotes the extension of 3′‐UTR of mRNAs. Although they have characteristics of long non‐coding RNAs, they instead act as antisense RNA to regulate gene transcription (Sun et al ., ). It could be possible that non‐canonical mRNA isoforms might, in some cases, act as miRNA repressors or other sorts of RNA regulators.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, PACs that do not map to the annotated regions might represent long non‐coding RNAs. In Arabidopsis, dehydration stress incites an extension of some 3´UTRs, yielding mRNAs that possess characteristics of long non‐coding RNAs (Sun et al , ). The 353 sense‐oriented unannotated PACs that lie within 2 kb of annotated genes (Table S4) may represent analogous Sorghum RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…A core component of the m 6 A methyltransferase complex in Arabidopsis At3g54170 Os06g27970 M 3 , N 4,6 , P 5 Růžička et al, 2017) 4,6 ;(Ferro et al, 2010) 5 FPA Encodes an homolog of RBM15 which induces 3′ UTR extension in Arabidopsis At2g43410 Os09g34070 ? (Batista, 2017;Sun et al, 2017) HAKAI Contains a conserved E3 ubiquitin ligase domain At5g01160 Os10g35190 N 4,6 (Růžička et al, 2017) 4,6 VIR Encodes a splicing/methylation factor homolog of the mammalian VIRILIZER At3g05680 Os03g35340 N 4,6 (Růžička et al, 2017) 4,6 Putative Erasers…”
Section: Gene Name Gene Annotationmentioning
confidence: 99%